FACTORS THAT INFLUENCE EMPLOYEE PERFORMANCE: SATISFACTION, COMMITMENT, MOTIVATION - Romiana Br Sihombing; Serma; Sahira; Putri Vebryani (Indonesian Journal of Social Sciences, Policy and Politics, 2025)
Employee performance plays a crucial role in shaping an organization's productivity and success. It is one of the essential components that determine an organization's success and efficiency. Studies show that job satisfaction, organizational commitment, and the drive to work meaningfully affect improvements in employee performance outcomes. This research aims to theoretically analyze the relationship between the three variables and employee performance. To achieve this goal, this study will use a literature review method. The method employed is a descriptive qualitative approach, and data collection involves a literature review of various academic sources, including books, national and international journals, and relevant scientific articles. Findings from the research reveal that occupational motivation is the primary driving force behind productive behavior, and job satisfaction is associated with positive feelings towards work. Additionally, organizational commitment demonstrates loyalty and emotional attachment to the company. All three are crucial in determining employee performance, particularly in terms of output standards, volume produced, and task efficiency. By employing the right psychological and managerial approaches, these findings are expected to provide a basis for developing plans to enhance employee performance.